Tantangan Akuntansi Syariah dalam Pengelolaan Rekening Investasi Berbagi Keuntungan pada Bank Islam - Nur Aida; Rayyan Firdaus (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Because interest-bearing deposits are not allowed by Islamic Sharia rules and principles, Islamic banks generally collect deposits in the form of profit-sharing investment accounts. These accounts differ from conventional deposits not only because of the profit-sharing nature of the returns they offer but also because the relationship between the customer and the bank is not a debt contract, so these deposits are not considered 'fixed capital.' (artinya, nasabah dapat menerima hasil negatif atau kerugian). This last characteristic poses serious regulatory issues in jurisdictions where bank deposits are legally required to have a definition of 'certain capital.' In general, the presence of such 'risk-bearing instruments' in the capital structure of Islamic banks complicates the assessment of their capital adequacy. Moreover, the fact that profit-sharing investment account holders are a type of equity investor without the governance rights held by creditors or shareholders poses a significant oversight problem. This article explains these issues in more detail and proposes a solution in the form of a structural distinction between Islamic banks in the narrow sense on one side, and entities managing profit-sharing investment accounts on the other.